Metatheoretical Linguistics: A Philosopher’s Guide - Konstantinos Voudouris; Niall Roe (Biolinguistics)
In this article, we summarise and critically evaluate Ryan Nefdt’s The Philosophy of Theoretical Linguistics: A Contemporary Outlook (2024). In this book, Nefdt brings the tools of philosophy to bear on contemporary linguistics, targeting perennial debates in syntax, semantics, pragmatics, phonology, and the evolution of language. In so doing, Nefdt sketches several tantalising paths for progress on these topics. Although some of Nefdt’s arguments are underdeveloped, this book serves as a worthwhile introduction to the philosophy of linguistics.